Diagnosis, Therapy and Follow-up of Cervical Cancer. Guideline of the DGGG, DKG and DKH (S3-Level, AWMF Registry No. 032/033OL, May 2021) – Part 1 with Recommendations on Epidemiology, Screening, Diagnostics and Therapy - Beckmann, Matthias; Stübs, Frederik; Koch, Martin; Mallmann, Peter; Dannecker, Christian; Dietl, Anna; Sevnina, Anna; Mergel, Franziska; Lotz, Laura; Hack, Carolin; Ehret, Anne; Gantert, Daniel; et al. (Geburtshilfe und Frauenheilkunde, 2022)
Aim This update of the interdisciplinary S3 guideline on the Diagnosis, Therapy and Follow-up of Cervical Cancer (AWMF Registry No. 032/033OL) was published in March 2021. This updated guideline was funded by German Cancer Aid (Deutsche Krebshilfe) as part of the German Guideline Program in Oncology. The guideline was coordinated by the German Society of Gynecology and Obstetrics (Deutsche Gesellschaft für Gynäkologie und Geburtshilfe, DGGG) and the Working Group on Gynecological Oncology (Arbeitsgemeinschaft Gynäkologische Onkologie, AGO) of the German Cancer Society (Deutsche Krebsgesellschaft, DKG). Method The process of updating the S3 guideline dating from 2014 was based on an appraisal of the available evidence using the criteria of evidence-based medicine, adaptations of existing evidence-based national and international guidelines or - if evidence was lacking - on a consensus of the specialists involved in compiling the update. After an initial review of the current literature was carried out according to a prescribed algorithm, several areas were identified which, in contrast to the predecessor version from September 2014, required new recommendations or statements which took account of more recently published literature and the appraisal of the new evidence. Recommendations The short version of this guideline consists of recommendations and statements on the epidemiology, screening, diagnostic workup and therapy of patients with cervical cancer. The most important new aspects included in this updated guideline include the newly published FIGO classification of 2018, the radical open surgery approach for cervical cancers up to FIGO stage IB1, and use of the sentinel lymph node technique for tumors ≤ 2 cm. Other changes include the use of PET-CT, new options in radiotherapy (e.g., intensity-modulated radiotherapy, image-guided adaptive brachytherapy), and drug therapies to treat recurrence or metastasis.
CRIS-Team Scopus Importer:2022-03-04
Keywords: cervical cancer; cervical intraepithelial neoplasia; follow-up; guideline; therapy